Particulate Matter Triggers Depressive-Like Response Associated With Modulation of Inflammatory Cytokine Homeostasis and Brain-Derived Neurotrophic Factor Signaling Pathway in Mice. (23rd April 2018) - Liu, Xuemei; Qian, Xin; Xing, Jing; Wang, Jinhua; Sun, Yixuan; Wang, Qin'geng; Li, Huiming
Abstract: Particulate matter (PM) exposure may contribute to depressive-like response in mice. However, few studies have evaluated the adaptive impacts of long-term PM exposure on depressive-like response associated with systemic inflammation and brain-derived neurotrophic factor (BDNF) signaling pathway. We studied the association among depressive-like behaviors, mRNA levels of pro and anti-inflammatory cytokines, and the expression of BDNF signaling pathway in mice by long-term PM exposure. C57BL/6 male mice were exposed to ambient air alongside control mice breathing air filtered through a high-efficiency air PM (HEPA) filter. Depressive-like behaviors were assessed together with proinflammatory, anti-inflammatory cytokine mRNA levels and the modulation of BDNF pathway in hippocampus and olfactory-bulb of mice exposed to PM for 4, 8, and 12 weeks. Exposure to HEPA-filtered air for 4 weeks may exert antidepressant like effects in mice. Proinflammatory cytokines were up-regulated while the expression of BDNF, its high-affinity receptor tropomyosin-related kinase B ( TrkB ), and the transcription factor (cyclic adenosine monophosphate)-response element-binding protein ( CREB ) were down-regulated in ambient air mice. However, after 8 weeks, there was no significant difference in the rate of depressive-like behaviors between the 2 groups. After 12 weeks, mice exposed to ambient air again had a higher rate of depressive-like behaviors, significant up-regulation of proinflammatory cytokines, down-regulation of interleukin-10, BDNF, TrkB, and CREB than HEPA mice. Ultrafine PM in brain tissues of mice exposed to ambient air was observed. Our results suggest continuous high-level PM exposure alters the depressive-like response in mice and induces a damage-repair-imbalance reaction.